Megatrends Asia : - Naisbitt, John (Simon & Schuster, 1996)
Writing with the combination of acute perceptions and broad sweep of his previous Megatrends bestsellers, Naisbitt describes the dramatic events that are now taking place in Asia as once isolated nation-states expand their individual economies and develop a powerful new synergy that works to their mutual benefit. Although the United States continues to focus on Europe, Naisbitt shows why the collapse of the Soviet.